Last days of Pompeii - Shelden, Olive Maria (My University, 1898)
Introduction: Pompeii now the “city of the dead,” was an ancient city of Campania, situated on the Bay of Naples, in that region noted for its beauty and picturesqueness, and being in a little valley at the foot of Vesuvius. At the date of the story, about nineteen centuries ago, when Rome was in the hautiest age of the Empire, in its luxury and power, Pompeii was a populous and flourishing place, a half-Grecian colony of Hercules, mingling the manners and costumes of Hellas with those of Italy. The worship of Isis, the favorite god of the Egyptians had been imported into Italy and was now the rage. The licentiousness of the priesthood and the false oracles were not yet unveiled, and the early struggles of Christianity with heathen superstition was just beginning.
Citation: Shelden, Olive Maria. Last days of Pompeii. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Pompeii; Italy; History; Theses; Manuscripts (documents)